A Review of Blockchain: How Does It Work, Applications, and Challenges - Ade Kurniawan; Winda Andrini Wulandari; Raymond Erz Saragih; Ihsan Verdian (Journal of Telematics and Informatics, 2020)
Behind Bitcoin’s, there is a technology that becomes its fundamental part, which is Blockchain. Bitcoin is the first cryptocurrency in the world. At present, blockchain technology is the subject of discussion and research among developers, business people and researchers. Basically, blockchain technology functions as a digital 'ledger' that records every transaction that occurs and what makes blockchain interesting is, data that has been recorded in it cannot be changed. Furthermore, various blockchain-based applications began to emerge, and are used in various fields, the first to implements blockchain technology is digital currency transactions, other fields, such as the Internet of Things, government, health services, education, and industries. However, like other emerging technologies, blockchain technology still faces several challenges such as scalability and security. To deepen the knowledge about blockchain technology, a literature study is needed using the Literature Review method. This research uses literature sources from Scopus reputable institutions, Thomson Reuters / Web of Science, Directory of Open Access Journals (DOAJ), EBSCO, and Google Scholar. The contribution of this paper is to convey how Blockchain technology works, the applications and challenges ahead that will be faced by blockchain technology.